Effect of sintering temperature on microstructure and mechanical properties of molded Martian and Lunar regolith. Issue 23 (1st December 2022) - Warren, Peter; Raju, Nandhini; Ebrahimi, Hossein; Krsmanovic, Milos; Raghavan, Seetha; Kapat, Jayanta; Ghosh, Ranajay
Abstract: Cylindrical specimens of Martian and Lunar regolith simulants were molded using a simple salt water binder and sintered at various temperatures for comparing microstructure, mechanical properties and shrinkage. Material microstructure are reported using optical microscope and material testing is done using an MTS universal testing machine. A total of twenty samples were made for the Mars global simulant (MGS-1), and twenty more using Lunar mare simulant (LMS-1). The samples were split into groups of five and the sintering profiles were varied for each group. The specimens were fabricated via an injection molding method, designed to replicate typical masonary units manufactured via Binder Jetting Technique (BJT), an important additive manufacturing (AM) technique. Results show that for both the Martian and Lunar regolith that the optimal sintering temperature was somewhere between 1100°C and 1200°C. The compressive strength for both the Martian and Lunar masonary samples, that received optimal sintering conditions, was determined to be sufficient for construction of extraterrestrial structures. This work demonstrates the feasibility of implementing an accessible in-situ binder material, for either Martian or Lunar regolith, in order to construct extra-terrestrial masonary structures. The work provides a feasible path towards the direct implementation of BJT for the manufacturing of either Lunar or Martian masonary prisms.